Correlations between major risk factors and closely related Mycobacterium tuberculosis isolates grouped by three current enotyping procedures: a population-based study in northeast Mexico - Peñuelas Urquides, Katia; Martínez Rodríguez, Herminia Guadalupe; Enciso Moreno, José Antonio; Molina Salinas, Gloria María; Silva Ramírez, Beatriz; Padilla Rivas, Gerardo Raymundo; Vera Cabrera, Lucio; Torres de la Cruz, Víctor Manuel; Martínez Martínez, Yazmín Berenice; Ortega García, Jorge Luis; Garza Treviño, Elsa Nancy; Enciso Moreno, Leonor; et al. (2014)
The characteristics of tuberculosis (TB) patients related to a chain of recent TB transmissions were investigated. Mycobacterium tuberculosis (MTB) isolates (120) were genotyped using the restriction fragment length polymorphism-IS6110 (R), spacer oligotyping (S) and mycobacterial interspersed repetitive units-variable number of tandem repeats (M) methods. The MTB isolates were clustered and the clusters were grouped according to the similarities of their genotypes. Spearman’s rank correlation coefficients between the groups of MTB isolates with similar genotypes and those patient characteristics indicating a risk for a pulmonary TB (PTB) chain transmission were analysed. The isolates showing similar genotypes were distributed as follows: SMR (5%), SM (12.5%), SR (1.67%), MR (0%), S (46.67%), M (5%) and R (0%). The remaining 35 cases were orphans. SMR exhibited a significant correlation (p < 0.05) with visits to clinics, municipalities and comorbidities (primarily diabetes mellitus). S correlated with drug consumption and M with comorbidities. SMR is needed to identify a social network in metropolitan areas for PTB transmission and S and M are able to detect risk factors as secondary components of a transmission chain of TB.